PENDAMPINGAN PEMAHAMAN KEKUATAN, PELUANG DAN PENDAPATAN PADA USAHA KERUPUK MARTABAK DI KATULISAN KASEMEN KOTA SERANG - Siti Fatonah; Syifa Nabilah; Ahmad Ridwan (JIPAM : Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The purpose of this study was to determine the strength of the martabak cracker product, to determine the opportunities possessed by the martabak cracker, and the last is to determine the net income obtained from daily and monthly sales of martabak crackers in the Katulisan Kasemen area of ​​Serang City.  This research method uses qualitative research methods with a descriptive approach. The data collection techniques used observation, interview and documentation techniques. The analysis used is a SWOT analysis in formulating a strategy for a product where with this analysis it can be seen to the maximum extent the strengths, opportunities, weaknesses and threats by suppressing the level of weaknesses and threats that may exist in every business run. The results show the strength (strength) of martabak crackers, namely the product is made with quality, healthy and suitable ingredients for consumption, martabak crackers are different from other types of crackers in that they have a darker color resembling a line on each side, the taste of martabak crackers is savory, the texture is crunchy and suitable. for all situations, the color of martabak crackers is very familiar because it has a common color, namely brownish yellow, the price of martabak crackers is very affordable by all people and competes with the same product. Opportunities (Opportunities) for martabak crackers, namely there are no martabak cracker products outside the city of Serang, so there is still a big opportunity if you expand your market share to the Serang district and other districts in the Banten province, it is still wide open to open resellers because the products are still obtained directly from producers, the price is still relatively cheap when compared to similar cracker products, increasing production capacity because the crackers always run out in a day. The net income earned every day is Rp. 490,000,-, and the monthly income is deducted from holidays, which is Rp. 12.740.000